Regular tree languages and quasi orders - Petković, Tatjana (Acta Cybernetica, 2006)
Regular languages were characterized as sets closed with respect to monotone well-quasi orders. A similar result is proved here for tree languages. Moreover, families of quasi orders that correspond to positive varieties of tree languages and varieties of finite ordered algebras are characterized.